Interrelationship of Nature and Women: Zora Neale Hurston Jonah Gourd Vine: Unveiling the Invisible: Zora Neale Hurston's Exploration of the Interrelationship between Nature and Women (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The most acclaimed Afro American writer of 20th Century Zora Neale Hurston had contributedsignificantly to voice out the atrocities inflicted on the weaker sex who led a life of absolute invisibility.These black women were helpless and adopted Voodoo as a magical craft to cast a spell on men to turnthem to grant their wishes. These females were nothing but a vulnerable victim at the hands of men whowere often indulged in all kinds of immoral activities, including extramarital affairs. The paper highlightsthe immoral activities of John the protagonist who gets trapped to evil fate on account of his ownimmoral activities.